Formulations And Solutions To Reduce The Minimum Interest Of Indonesian Community In Partnering With Sharia Banking - Rizka Rizka; Bahtiar Hakim; Muhammad Sholahuddin (International Journal of Social Service and Research, 2022)
Indonesian society is known as a society with complex heterogeneity, including a very dynamic structure in terms of political, economic, socio-cultural, and legal aspects. The enormous number of Muslim populations in Indonesia is the reason for continuing to strive for the development of the sharia economy which in its journey has met several obstacles. The dominance of the theory of capitalism in Indonesia, which originates from West and is even the focus of almost all countries today, has created economic injustice, because it only benefits West through the hegemony of paper currency and usury lending system. Economic theories formulated by experts are not able to present a just and civilized economic order for society, and even create a dichotomy between the interests of individuals, society, the state and relations between countries. In addition, it is also unable to maintain the sustainability of natural resources. According to the Islamic worldview, the capitalist economic system that is ingrained in Indonesia is a system that must be Islamized. So, of course the aspired economic theory is an economic system that can create justice and mutual prosperity accompanied by the blessings of the world and the hereafter. The theory is Islamic economics is sourced from Allah's law which brings justice and prosperity to all humankind, because Islam is a mercy to all of nature.